Submicroscopic changes of type II alveolocytes in the late development of experimental acute pancreatitis - Liubomyr Zaiats; Olga Pasichnyk; Walery Zukow (Kazimierz Wielki University, 2024)
Background. Today, acute pancreatitis is one of the most common and severe visceral disorders in patients worldwide. The aim of the work was to study the dynamics of ultrastructural changes of type II alveolocytes in the long-term periods of development of experimental acute pancreatitis. Material and methods. The experiments were carried out on 54 white Wistar male rats weighing 180-220 g. The animals were divided into three groups: first - intact, second - control, third - experimental with a model of acute pancreatitis, which was reproduced by intraperitoneal administration of a 20% solution of L-arginine at a total dose of 5 g/kg at one-hour interval. The control group of animals was intraperitoneally injected with an equivalent dose of isotonic sodium chloride solution. All research were performed under sodium thiopental anesthesia at the rate of 60 mg/kg body weight. Lung tissue for electron microscopic examination was collected from the lower lobe of the left lung at 3-5 and 7 days. Pieces of lung tissue measuring 1×1×1 mm were fixed in a 2.5% glutaraldehyde solution, followed by additional fixation in a 1% osmium tetroxide solution. After dehydration, the material was poured into Epon-Araldite. Sections with a thickness of 20-50 nm obtained on "Tesla BS-490" ultramicrotome were studied in a PEM-125K electron microscope. Results. It was found that three days after the start of the study, along with dystrophic-destructive changes, type II alveolocytes in a state of increased functional activity were observed. Continuation of the experiment (5 days) leads to the progression of ultrastructural changes in type II alveolocytes are determined, which are most pronounced on the 7 day of the study. Conclusion. Acute experimental pancreatitis is accompanied by marked changes in the ultrastructural structure of type II alveolocytes. The nature and severity of structural changes of type II alveolocytes depends on the duration of the course of arginine-induced acute pancreatitis.